Physical activity, mediating factors and risk of colon cancer: insights into adiposity and circulating biomarkers from the EPIC cohort - Aleksandrova, K; Jenab, M; Leitzmann, M; Bueno-De-Mesquita, B; Kaaks, R; Trichopoulou, A; Bamia, C; Lagiou, P; Rinaldi, S; Freisling, H; Carayol, M; Pischon, T; et al. (Oxford University Press, 2017)
Background: There is convincing evidence that high physical activity lowers the risk of colon cancer; however, the underlying biological mechanisms remain largely unknown. We aimed to determine the extent to which body fatness and biomarkers of various biologically plausible pathways account for the association between physical activity and colon cancer. Methods: We conducted a nested case-control study in a cohort of 519 978 men and women aged 25 to 70 years followed from 1992 to 2003. A total of 713 incident colon cancer cases were matched, using risk-set sampling, to 713 controls on age, sex, study centre, fasting status and hormonal therapy use. The amount of total physical activity during the past year was expressed in metabolic equivalent of task [MET]-h/week. Anthropometric measurements and blood samples were collected at study baseline. Results: High physical activity was associated with a lower risk of colon cancer: relative risk ≥91 MET-h/week vs <91 MET-h/week = 0.75 [95% confidence interval (CI): 0.57 to 0.96]. In mediation analyses, this association was accounted for by waist circumference: proportion explained effect (PEE) = 17%; CI: 4% to 52%; and the biomarkers soluble leptin receptor (sOB-R): PEE = 15%; 95% CI: 1% to 50% and 5-hydroxyvitamin D (25[OH]D): PEE = 30%; 95% CI: 12% to 88%. In combination, these factors explained 45% (95% CI: 20% to 125%) of the association. Beyond waist circumference, sOB-R and 25[OH]D additionally explained 10% (95% CI: 1%; 56%) and 23% (95% CI: 6%; 111%) of the association, respectively. Conclusions: Promoting physical activity, particularly outdoors, and maintaining metabolic health and adequate vitamin D levels could represent a promising strategy for colon cancer prevention.